Home pesticide exposures and risk of childhood leukemia: Findings from the childhood leukemia international consortium. Issue 11 (26th June 2015) - Bailey, Helen D.; Infante‐Rivard, Claire; Metayer, Catherine; Clavel, Jacqueline; Lightfoot, Tracy; Kaatsch, Peter; Roman, Eve; Magnani, Corrado; Spector, Logan G.; Th. Petridou, Eleni; Milne, Elizabeth; Dockerty, John D.; et al.
Abstract : Some previous studies have suggested that home pesticide exposure before birth and during a child's early years may increase the risk of childhood leukemia. To further investigate this, we pooled individual level data from 12 case–control studies in the Childhood Leukemia International Consortium. Exposure data were harmonized into compatible formats. Pooled analyses were undertaken using multivariable unconditional logistic regression. The odds ratio (ORs) for acute lymphoblastic leukemia (ALL) associated with any pesticide exposure shortly before conception, during pregnancy and after birth were 1.39 (95% confidence interval [CI]: 1.25, 1.55) (using 2, 785 cases and 3, 635 controls), 1.43 (95% CI: 1.32, 1.54) (5, 055 cases and 7, 370 controls) and 1.36 (95% CI: 1.23, 1.51) (4, 162 cases and 5, 179 controls), respectively. Corresponding ORs for risk of acute myeloid leukemia (AML) were 1.49 (95% CI: 1.02, 2.16) (173 cases and 1, 789 controls), 1.55 (95% CI: 1.21, 1.99) (344 cases and 4, 666 controls) and 1.08 (95% CI: 0.76, 1.53) (198 cases and 2, 655 controls), respectively. There was little difference by type of pesticide used. The relative similarity in ORs between leukemia types, time periods and pesticide types may be explained by similar exposure patterns and effects across the time periods in ALL and AML, participants' exposure to multiple pesticides, or recall bias. Although some recall bias is likely, until a better study design can be found to investigate the associations between home pesticide use and childhood leukemia in an equally large sample, it would appear prudent to limit the use of home pesticides before and during pregnancy, and during childhood. Abstract : What's new? Some studies have suggested that early pesticide exposure may increase the risk of childhood leukemia. In this investigation, the authors pooled individual level data from twelve previous case‐control studies to further examine this question. They found an association between home pesticide exposure before birth and during a child's early years and acute lymphoblastic leukemia (ALL) and with exposure before birth and acute myeloid leukemia (AML). These results indicate that it would be prudent for parents to limit the use of home pesticides before and after a child's birth.